Proposta de melhoria na construtibilidade de edificações a partir da implantação de banco de lições aprendidas - Silva, Frederico Augusto Coelho da (2018)
Civil construction, sub-sector buildings, has been characterized by low global productivity and refractory to innovation. Delays in schedule, surplus costs, which generate low productivity and compromise the quality of the works, have, among other causes, low integration between the various stages of the project life cycle as well as the loss of experience and knowledge to build, which does not apply as information in the initial stages of the enterprises. In this context, the objective of this work is to produce a tool for recording and consulting lessons learned, aiming to improve the constructability of new and future projects. The research was developed in 6 stages: bibliographic review on the theme; selection of classification parameters of lessons learned; identification of barriers to organizational learning; development of the model architecture; Validation of the model in the professional and academic community and publication of the artifact. The obtained results point to the suitability of the artifact to the objective, with possible improvements expected by the use of more efficient IT tools. The artifact brings as innovation the combination of mechanical and organic approaches in knowledge management, as well as strategies to attenuate the barriers to knowledge sharing.